2019
DOI: 10.1021/acscatal.9b01093
|View full text |Cite
|
Sign up to set email alerts
|

Edge-Enhanced Oxygen Evolution Reactivity at Ultrathin, Au-Supported Fe2O3 Electrocatalysts

Abstract: Transition metal oxides have gained attention as promising oxygen evolution reaction (OER) electrocatalysts in alkaline electrolytes, but heterogeneities in typical catalyst samples often obscure key structure–property relationships that are essential for developing higher performance materials. Here, we have combined ultrahigh vacuum surface science techniques, electrochemical measurements, and density functional theory (DFT) to quantify structure-dependent OER activity in a series of well-defined electrocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…The metallic Au surface post‐electrochemistry was verified by XPS peak fitting of the Au 4 f peak in Figure a. Perhaps it is the continual reformation of the AuO x −FeO x H y interface that results in highly‐active sites for the OER, as suggested by both our previous work and other reports that showed high activity for Fe atoms substituted at the surface of Au 2 O 3 and edges sites at the Fe 2 O 3 −Au interface . Redox features are also observed for all other substrates except for C (Figures , 2, and S5).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The metallic Au surface post‐electrochemistry was verified by XPS peak fitting of the Au 4 f peak in Figure a. Perhaps it is the continual reformation of the AuO x −FeO x H y interface that results in highly‐active sites for the OER, as suggested by both our previous work and other reports that showed high activity for Fe atoms substituted at the surface of Au 2 O 3 and edges sites at the Fe 2 O 3 −Au interface . Redox features are also observed for all other substrates except for C (Figures , 2, and S5).…”
Section: Resultssupporting
confidence: 70%
“…Recently, Kauffman et al. found that edge sites at the interface of Au and Fe 2 O 3 showed high activity for the OER …”
Section: Introductionmentioning
confidence: 99%
“…The continuous CMOH (1 × 1 cm 2 ) electrodes and discontinuous ones (25 isolated pieces with a total coverage area of 1 cm 2 identical to the coverage of continuous ones) were tested for electrocatalytic OER comparison ( Figure a,b). The linear sweep voltammetry (LSV) results show a similar trend that the discontinuous CMOH on both the substrates exhibits greater OER performance as the overpotentials lowered than the continuous ones (Figure a,b), indicating that the edge enhancement may generally occur independent on specific substrate materials, although some specific case on gold has been reported . In addition, the varied distance between each isolated CMOH pieces on the both substrates shows no appreciable influence on the LSV results (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 63%
“…As shown in Figure b, at the beginning of the conditioning, all of the samples exhibit the increasing of current density in different magnitude, which roughly saturated at the first 5 h conditioning and reached the values of 75.02 mA cm −2 (CMOH‐py‐S), 29.03 mA cm −2 (CMOH‐py‐M), 10.70 mA cm −2 (CMOH‐py‐L), and 5.45 mA cm −2 (CMOH‐py‐XL), corresponding to the current enhancement of 1500%, 580%, 214%, and 109%, respectively, by referencing the initial current density (5 mA cm −2 ). Such the unusually high increase of 1500% OER current density in electrochemical conditioning has not been reported in the other similar systems during the conditioning . The first 5 h stage of current climbing may reflect the intrinsic capacity of Co 3+ /Co 4+ and phase activation; the upper limits of current density saturation may suggest that certain quantity of idle sites is not allowed to be further activated regardless of extension of the conditioning time.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation